IN-VIVO AND IN-SILICO ANALYSIS OF ANTI- INFLAMMATORY, ANALGESIC, AND ANTI PYRETIC ACTIVITIES OF CITRUS PARADISI LEAF EXTRACT - Naureen Zahra; Tahira Fareed; Muhammad Hamza; Basit Zeeshan; Abid Sarwar; Tari Aziz; Metab Alharbi; Abdulrahman Alshammari (Journal of the Chilean Chemical Society, 2023)
Medicinal plants recently gained attention due to the presence of many phytochemicals involved in various therapeutical activities. The main aim of this study was to determine the in-vivo and in-silico anti-inflammatory, analgesic, and anti-pyretic effects of Citrus paradisi leaf ethanolic extract using albino rats (n = 36). For inducing inflammation, pain, and fever in albino rat’s carrageenan, acetic acid dilution in distilled water and yeast dilution in saline were used. The four different concentrations (50, 100, 200, and 400mg/kg) of ethanolic extract of Citrus paradisi leaf were used to prevent inflammation, pain, and fever. Diclofenac and paracetamol were used as standard drugs in this study. The ethanolic extract of Citrus paradisi leaf showed efficient anti-pyretic and anti-inflammatory inhibition (90% and 80%, respectively) but less efficient analgesic inhibition (36%). Similarly, in-silico study was done using leaf bioactive compounds such as linalool, beta-pinene, geraniol, citral, and terpinene-4-ol as ligand molecules and proteins for anti-inflammatory, analgesic, and anti-pyretic activity were PTGS2, TRPV4, and TLR2, respectively. The process of docking was done using ligand and protein molecules. The results of in-silico study were the same as in-vivo study; the binding energy values of anti-inflammatory and anti-pyretic activity were more efficient than an analgesic. In summary, the ethanolic extract of Citrus paradisi leaf in in-silico and in-vivo studies  proved less efficient against pain while more efficient against inflammation and fever.